2021
DOI: 10.1002/ange.202109068
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Hydrogen‐Bonded Organic Frameworks (HOFs) Used for Target‐Specific Amyloid‐β Photooxygenation in an Alzheimer's Disease Model

Abstract: Phototherapyh as emerged as ap owerful approach for interrupting b-amyloid (Ab)s elf-assembly.H owever, deeper tissue penetration and safer photosensitizers are urgent to be exploited for avoiding damaging nearby normal tissues and improving therapeutic effectiveness.Ahydrogen-bonded organic framework (HOF)-based NIR-II photooxygenation catalyst is presented here to settle the abovementioned challenges.B ye ncapsulating the pyridinium hemicyanine dye DSM with alarge two-photon absorption (TPA) cross-section

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…39–41 The cavities with size accommodated to the Aβ peptide sequence and functional groups that interact with specific sites on the Aβ chain could permit synergetic inhibitory effects on Aβ fibrillation. 12,42,43 Overall, our prepared SP-COFs may be superior in terms of adsorption capacity and target specificity, which are capable of enhancing the restricted-access adsorption force on Aβ through host–guest recognition and specifically capturing the positively charged amino acid sites on the Aβ sequence.…”
Section: Introductionmentioning
confidence: 93%
“…39–41 The cavities with size accommodated to the Aβ peptide sequence and functional groups that interact with specific sites on the Aβ chain could permit synergetic inhibitory effects on Aβ fibrillation. 12,42,43 Overall, our prepared SP-COFs may be superior in terms of adsorption capacity and target specificity, which are capable of enhancing the restricted-access adsorption force on Aβ through host–guest recognition and specifically capturing the positively charged amino acid sites on the Aβ sequence.…”
Section: Introductionmentioning
confidence: 93%
“…[261,262] Gobbi et al [263] reported that nanoliposomes containing phosphatidic acid (PA) and targeting peptides KLVFFAED (KD8) was conjugated to DSM@n-HOF-6 (DSM@n-HOF-6@KD8). [274] Up-conversion fluorescence of DSM could be absorbed by TCPP to generate 1 O 2 for Aβ oxygenation, DSM@n-HOF-6@KD8 could inhibit fibrillation of Aβ monomers and reduce cytotoxicity of Aβ by photooxygenation. The application of polystyrene nanoparticles and upconverting nanoparticles in amyloid diseases has also been reported.…”
Section: Liposomesmentioning
confidence: 99%
“…In recent years, HOFs, as a new type of porous framework material, have been explored in gas separation, [48][49][50] catalysis, [51][52][53] gas storage, [54][55][56][57] fluorescence detection [58][59][60][61][62][63][64][65] and enzyme encapsulation. 66 Furthermore, the metal-free nature endows HOFs with considerable biocompatibility and low toxicity; thus HOFs could be an excellent candidate for the detection of drugs and biomarkers. However, the stability of HOF sensors in water is also a critical prerequisite because the sensing processes of most biologically related species take place in water.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, HOFs, as a new type of porous framework material, have been explored in gas separation, 48–50 catalysis, 51–53 gas storage, 54–57 fluorescence detection 58–65 and enzyme encapsulation. 66…”
Section: Introductionmentioning
confidence: 99%